2011
DOI: 10.1007/s00213-011-2358-5
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin occasioned mystical-type experiences: immediate and persisting dose-related effects

Abstract: Rationale This dose-effect study extends previous observations showing that psilocybin can occasion mystical-type experiences having persisting positive effects on attitudes, mood, and behavior. Objectives This double-blind study evaluated psilocybin (0, 5, 10, 20, 30 mg/70 kg, p.o.) administered under supportive conditions. Methods Participants were 18 adults (17 hallucinogen-naïve). Five 8-hour sessions were conducted individually for each participant at 1-month intervals. Participants were randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

83
754
14
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 721 publications
(917 citation statements)
references
References 28 publications
83
754
14
19
Order By: Relevance
“…In another study, Griffiths et al (2011) found that administration of psilocybin, at the two highest doses given, produced mystical-type experiences in 72% of volunteers. Both 1 month and 14 months after psilocybin administration, participants attributed ongoing improvement to domains such as mood, behavior, and attitudes to the psilocybin experience (Griffiths et al, 2011, p. 649).…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…In another study, Griffiths et al (2011) found that administration of psilocybin, at the two highest doses given, produced mystical-type experiences in 72% of volunteers. Both 1 month and 14 months after psilocybin administration, participants attributed ongoing improvement to domains such as mood, behavior, and attitudes to the psilocybin experience (Griffiths et al, 2011, p. 649).…”
mentioning
confidence: 95%
“…While there are other mushrooms that reportedly produce psychedelic effects, such as Fly Agaric and Panther Caps (Stafford, 1992), the most prolific psychedelic mushrooms are those containing psilocybin (Stafford, 1992;Inaba and Cohen, 2004). Mushrooms containing psilocybin were likely the most commonly used in an organized religious or spiritual manner for thousands of years (Stafford, 1992;Inaba and Cohen, 2004;Sessa, 2005;Griffiths et al, 2006Griffiths et al, , 2008Griffiths et al, , 2011. Based on differing reports, there are somewhere between 80 and 200 species of psilocybin-containing mushrooms (Stafford, 1992;Inaba and Cohen, 2004), with more recent reports suggesting the latter number.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Spiritual experiences are not rare, with five to forty percent of the general population reporting having had at least one spiritual or mystical experience (Allman et al, 1992;Davis & Smith, 1985;Greeley, 1974;Ring, 1985;Thomas & Cooper, 1978). Indeed, spiritual practices such as prayer, meditation, or entheogen use are associated with increased numbers of spiritual or mystical experiences (e.g., Lyvers & Meester, 2012;Walsh & Vaughan, 1991), and the occurrence of these experiences is correlated with wellbeing (e.g., Griffiths et al, 2011;Griffiths, Richards, Johnson, McCann, & Jesse, 2008;Griffiths, Richards, McCann, & Jesse, 2006;Hood, 1977;Maslow, 1994).…”
Section: Spiritualitymentioning
confidence: 99%